Design and development of remote measurement for prime mover using Arduino and FR hope RFM12B / Mohd Akmal Mhd Yusoff - Mohd Akmal, Mhd Yusoff (2013)
This project aims to develop a remote measurement system for agricultural prime mover for in-field testing. The system is important especially for government agency such as MARDI which is entrusted to carry out research and development in agriculture including developing agricultural prime mover. RF system has been chosen as the remote wireless system to be used in this project. The hardware system consists of a measurement system, a transmitter and receiver system and a data monitoring system. The measurement system consists of Honeywell 1228-2K Torque sensor & FUTEK CSG110 Strain gauge amplifier. The Honeywell torque sensor was chosen because it is a general purpose torque sensor which is able to monitor start up, running and stall torque levels and rotational speed. Besides that, it also has low nonlinearity, repeatability and hysteresis specifications. The FUTEK amplifier is necessary because of the limited ADC resolution of our Arduino UNO. The transmitter and receiver system consists of HopeRF RFM12B-433-D RF module and Arduino UNO microcontroller. The RFM12B is a transceiver module which can either transmit or receive RF signal. It was chosen because it is cheap and secure, has medium range and able to transmit multiple data at the same time. Arduino UNO was chosen because it is easily configured, widely available, cheap and fully capable of executing the tasks expected of a microcontroller in this project. The data monitoring system is developed using National Instrument LabVIEW. It was chosen because its graphical programming is more intuitive and easier to develop than traditional textual programming.The developed system has been tested and proven to be able to carry out decent measurement of two simultaneous data from a range of 100 meters. However, to improve the system, more tests need to be done to determine if more data could be sent at the same time.